2021
DOI: 10.3389/fgene.2021.663746
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Loss-of-Function MKRN3 Variant in a Chinese Patient With Familial Precocious Puberty: A Case Report and Functional Study

Abstract: Background: Central precocious puberty (CPP) is one of the most common and complex problems in clinical pediatric endocrinology practice. Mutation of the MKRN3 gene can cause familial CPP.Methods and Results: Here we reported a Chinese patient bearing a novel MKRN3 mutation (c.G277A/p.Gly93Ser) and showing the CPP phenotype. Functional studies found that this mutation of MKRN3 attenuated its autoubiquitination, degradation, and inhibition on the transcriptional activity of GNRH1, KISS1, and TAC3 promoters.Conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…When similar in vitro ubiquitination reactions were performed with wild-type MKRN3 or mutants (Cys340Arg, Arg365Ser, Phe417Ile, His420Gln) (Figure 2), it was evident that disease-causing mutations in the RING domain or C-terminal region compromised autoubiquitination of MKRN3 (18). These data suggested that CPP-associated MKRN3 mutations may stabilize the MKRN3 protein by altering the activity of E3 ligase (17,18,25). This would lead to a subsequent reduction in autoubiquitination and a slower proteasome-mediated degradation.…”
Section: Ubiquitination and Autoubiquitination Activitymentioning
confidence: 87%
“…When similar in vitro ubiquitination reactions were performed with wild-type MKRN3 or mutants (Cys340Arg, Arg365Ser, Phe417Ile, His420Gln) (Figure 2), it was evident that disease-causing mutations in the RING domain or C-terminal region compromised autoubiquitination of MKRN3 (18). These data suggested that CPP-associated MKRN3 mutations may stabilize the MKRN3 protein by altering the activity of E3 ligase (17,18,25). This would lead to a subsequent reduction in autoubiquitination and a slower proteasome-mediated degradation.…”
Section: Ubiquitination and Autoubiquitination Activitymentioning
confidence: 87%
“…Since 2013, a total of 50 MKRN3 loss-of-function variants have been reported in the literature [4,[18][19][20][21][22]. There are 2 apparent hot spots.…”
Section: Discussionmentioning
confidence: 99%
“…( 16 ) reported four pathogenic variants of MKRN 3 in familial CPP. Variants, including whole gene deletions, have been identified since then in > 100 patients with familial and/or idiopathic CPP, the most frequently identified CPP worldwide ( 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ).…”
Section: Makorin Ring Finger Protein 3 (Mkrn3)mentioning
confidence: 99%
“…2 . These variants include a gene deletion, six promoter region abnormalities, and five nonsense, 13 frameshift, and 31 missense variants ( 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ). In vitro studies have shown that the promoter activity of MKRN3 is reduced in variants with promoter region abnormalities than that in wild-type ( 37 , 40 , 42 ).…”
Section: Makorin Ring Finger Protein 3 (Mkrn3)mentioning
confidence: 99%